Plotting Your Job Hunt: The Use of Visual Timeline for Investigating the Job Search Process - Estrada, Natalia (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – This article discusses the use of a visual timeline activity in qualitative research investigating a process. This was part of a larger project exploring the experience of former library staff and their searches for academic librarian positions. It will also discuss the impact a visual method had in shaping the quality of the data.Methods – In 2023, the author conducted in-depth virtual interviews with 22 former library staff working in U.S.-based academic libraries about their experiences applying for academic librarian positions. A timeline worksheet was incorporated into the interviews, in which participants were asked to chronologically plot out their searches, as well as discuss significance of their selections. Both transcripts and timelines were analyzed using inductive thematic analysis, with the derived codes applied to both. Timelines were analyzed for visual connection to themes.Results – Participants used the timelines as a way to explain steps taken during their job searches, eventually leading to the start of their new jobs. Completing the activity helped participants recall moments from their searches during the interview. They also used the visual format to express the emotions they felt and their sense of passing time. Issues that arose while conducting the activity included some participants’ fears of “doing [the activity] wrong,” as well as limitations of the digital tool used to lead the interviews.Conclusion – Qualitative research in library science can benefit from the use of visual methods like timelines, especially for research on procedural aspects of working in academic librarianship. While practical matters such as extra time and material needs may hamper a researcher’s desire to use them, visual data can supplement oral interview transcripts.